2016
DOI: 10.1128/jvi.01053-16
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Cholesterol Transport Inhibitor U18666A Inhibits the Exosome-Dependent Release of Mature Hepatitis C Virus

Abstract: Hepatitis C virus (HCV) particles are described as lipoviroparticles which are released similarly to very-low-density lipoproteins (VLDLs). However, the release mechanism is still poorly understood; the canonical endoplasmic reticulum-Golgi intermediate compartment (ERGIC) pathway as well as endosome-dependent release has been proposed. Recently, the role of exosomes in the transmission of HCV has been reported. Only a minor fraction of the de novo-synthesized lipoviroparticles is released by the infected cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 69 publications
5
70
0
1
Order By: Relevance
“…This reasoning also applies to a recent study by Mankouri et al, in which they conclude that the inhibition of Rab GTPase did not affect VLDL secretion and therefore that VLDLs are not associated with HCV secretion (28). Some studies implicated noncanonical secretion in HCV egress involving the endosomal compartments, autophagosomes, endocytic machinery, and ESCRT proteins (35)(36)(37)49). The presence of complex glycans on virus-associated glycoproteins substantiates that HCV virions traverse through the Golgi apparatus (43).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This reasoning also applies to a recent study by Mankouri et al, in which they conclude that the inhibition of Rab GTPase did not affect VLDL secretion and therefore that VLDLs are not associated with HCV secretion (28). Some studies implicated noncanonical secretion in HCV egress involving the endosomal compartments, autophagosomes, endocytic machinery, and ESCRT proteins (35)(36)(37)49). The presence of complex glycans on virus-associated glycoproteins substantiates that HCV virions traverse through the Golgi apparatus (43).…”
Section: Discussionmentioning
confidence: 75%
“…Intriguingly, the endocytic and endosomal sorting complex required for transport (ESCRT) machineries have also been implicated in HCV secretion (35,36). The intracellular cholesterol transport inhibitor U18666A promotes the accumulation of HCV particles in autophagosomal and exosomal structures, reflecting the involvement of exosomes in HCV secretion (34,37).…”
mentioning
confidence: 99%
“…Recent findings have suggested that exosomes could contain HCV particles or its genome to support the infective transmission between hepatocytes . Further, a recent study using an MVB inhibitor found that at least a fraction of mature HCV particles are released by MVBs . In that study, it was suggested that HCV particles are assembled in a membranous web of the ER that could be transported to an MVB compartment.…”
Section: Background and Structure Of Hepatitis Virusesmentioning
confidence: 99%
“…), it remains undetermined how the viral envelope proteins are transported onto MVBs. Figure depicts published images of confocal microscopy or TEM, showing that proteins or particles of hepatitis viruses are found in MVBs . The multisubunit membrane remodeling complex termed endosomal sorting complexes required for transport machinery (ESCRT) catalyzes the biogenesis of ILVs.…”
Section: Background and Structure Of Hepatitis Virusesmentioning
confidence: 99%
See 1 more Smart Citation